2009
DOI: 10.1111/j.1749-6632.2009.04669.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Damage Progression in Portuguese Patients with Systemic Lupus Erythematosus

Abstract: Patients with systemic lupus erythematosus (SLE) have a longer life expectancy. The occurrence of irreversible damage has become a major concern. The present study assessed damage progression in patients with SLE over a 2-year period and identified baseline features associated with damage accrual. Two hundred and twenty-one patients that fulfilled criteria for SLE and had a follow-up longer than 6 months were enrolled. Demographic, clinical, and immunological data were collected at baseline. Accumulated organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…5 Such an association between aPL and damage was recently confirmed by other studies, which nevertheless had some of the previously described methodological limitations. [7][8][9] We also confirmed the previous observations that SDI progressively increases over time and that patients with male sex and older age at diagnosis have an increased risk of experiencing such progression. 14 The lack of association between damage accrual and ethnicity could be explained by the fact that, despite being multiethnic, our cohort was mainly represented by Caucasians, and was therefore unable to demonstrate a difference among different ethnic groups, even though a shorter disease duration at registry entry, a possible indirect sign of more active disease that can increase the risk of damage, 14 showed an association with damage progression in the univariate analysis, which was not confirmed by the GEE model.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…5 Such an association between aPL and damage was recently confirmed by other studies, which nevertheless had some of the previously described methodological limitations. [7][8][9] We also confirmed the previous observations that SDI progressively increases over time and that patients with male sex and older age at diagnosis have an increased risk of experiencing such progression. 14 The lack of association between damage accrual and ethnicity could be explained by the fact that, despite being multiethnic, our cohort was mainly represented by Caucasians, and was therefore unable to demonstrate a difference among different ethnic groups, even though a shorter disease duration at registry entry, a possible indirect sign of more active disease that can increase the risk of damage, 14 showed an association with damage progression in the univariate analysis, which was not confirmed by the GEE model.…”
Section: Discussionsupporting
confidence: 89%
“…The effect of antiphospholipid antibodies (aPL) on organ damage in systemic lupus erythematosus (SLE) patients remains unclear, as a limited number of studies with inconsistent findings are available in the literature. [1][2][3][4][5][6][7][8][9] These studies also have methodological limitations, as in most cases the three standard aPL tests (lupus anticoagulant (LA), anticardiolipin (aCL), and anti-b 2 -glycoprotein I antibodies (ab 2 GPI)) were not tested, and/or clinically significant aPL profiles, i.e. persistent, moderate-to-high titers, as recommended by the International Classification Criteria for Antiphospholipid Syndrome (APS), 10 were not included.…”
Section: Introductionmentioning
confidence: 99%
“…Reports in Afro-Caribbean SLE patients indicate that anti-Sm, anti-RNP and anti-Ro are more prevalent than in those with European ancestry. 30,31,34 As previously observed, [29][30][31]34,36 the Afro-Caribbean SLE patients in our study had the greatest prevalence of anti-Sm antibodies (37.5%), which were much less common in the other groups (European 9.5%, East Asian 17.6% and South Asian 14.3%).…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, we lack evidence of reproducible trends and of possible etiologic factors that could help us to interpret the current results. However, there are data from large collections of European SLE patients that support the difference we have found: two collections of Spanish SLE patients showed a prevalence of oral ulcers of 46.4% and 54.3% (of 462 and 490 patients, respectively) [24] , and a study of 544 Portuguese SLE patients reported a prevalence of 45% [25] ; whereas the Euro-Lupus study showed a prevalence of 12.5% (of 1000 patients from all over Europe) [26] .…”
Section: Discussionsupporting
confidence: 63%